Adults’ Cognitive and Socioemotional Skills and their Labor Market Outcomes in Colombia - Acosta, Pablo; Muller, Noel; Sarzosa, Miguel (World Bank, Washington, DC, 2015)
Previous research has shown that people with higher cognitive skills (mental abilities) and socioemotional skills (behaviors and personality) get better labor market outcomes. It is unclear, however, if this conclusion applies to low- and middle-income countries, given that existing literature builds on studies that are dominantly about highincome countries. In this paper, we explore how cognitive and socioemotional skills of adults, ages 15–64, relate to their labor market outcomes in the context of Colombia. Controlling for a range of confounding factors in a crosssectional survey, we do find that adults with higher skills also have better outcomes, while cognitive and socioemotional skills correlate with different ones and seemingly through different channels. Adults with higher cognitive skills have better jobs (with higher earnings, more formal, and highskilled) and are more likely to complete tertiary education. Socioemotional skills correlate more modestly with having a better job but more strongly with labor market participation and tertiary-education completion. Results suggest that adults with both cognitive and socioemotional skills tend to do better in the labor market and that policies boosting the development of both types may be beneficial in Colombia.